Atmospheric mass loss and stellar wind effects in young and old systems - II. Is TOI-942 the past of TOI-421 system? - Kubyshkina, Daria (2022)
The two planetary systems, TOI-942 and TOI-421, share many similar characteristics, apart from their ages (50 Myr and 9 Gyr). Each of the stars hosts two sub-Neptune-like planets at similar orbits and in similar mass ranges. In this paper, we aim to investigate whether the similarity of the host stars and configuration of the planetary systems can be taken as proof that the two systems were formed and evolved in a similar way. In paper I of this series, we performed a comparative study of these two systems using three-dimensional (3D) modelling of atmospheric escape and its interaction with the stellar wind, for the four planets. We demonstrated that though the strong wind of the young star has a crucial effect on observable signatures, its effect on the atmospheric mass loss is minor in the evolutionary context. Here, we use atmosphere evolution models to track the evolution of planets in the younger system TOI-942 and also to constrain the past of the TOI-421 system. We demonstrate that despite all the similarities, the two planetary systems are on two very different evolutionary pathways. The inner planet in the younger system, TOI-942, will likely lose all of its atmosphere and become a super-Earth-like planet, while the outer planet will become a typical sub-Neptune. Concerning the older system, TOI-421, our evolution modelling suggests that they must have started their evolution with very substantial envelopes, which can be a hint of formation beyond the snow line.